PENGARUH MUTU PELAYANAN PERPUSTAKAAN TERHADAP KECEPATAN MEMPEROLEH INFORMASI BAHAN PUSTAKA BAGI MAHASISWA PRODI MPI ANGKATAN 2018 DI IAIN MADURA - Tukad Adi Wijaya; Mohammad Thoha (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2020)
Service is an activity whose implementation is carried out by holding relationships, both directly and indirectly. The service referred to here is how the service process is implemented and carried out in the library of IAIN Madura to facilitate information retrieval of library materials for students, especially MPI study program students in class 2018. This is evident from the results of statistical analysis showing that the work r 0.622 is consulted with product criticism moment at the value of N = 32 with the value